PENERAPAN MODEL PEMBELAJARAN PAIR CHECK MENGGUNAKAN MEDIA PAPAN BACA TERHADAP KETERAMPILAN MEMBACA PESERTA DIDIK KELAS 2 SD MUHAMMADIYAH 08 MEDAN - Mutia Saragih, Mutia; Nazwa Resya Afnenda; Arza Ratu Zahra; Melyani Sari Sitepu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research discusses the use of the pair check method using reading boards as a medium to improve students' reading skills. The purpose of this research is to determine and describe the effectiveness of the Pair Check learning model using reading boards in improving the reading skills of 2nd-grade elementary school students. This research was conducted using the Classroom Action Research method with a quantitative approach. The quantitative research method is the basis for the development of scientific knowledge. The low ability of students' reading comprehension is still a concern, so an effective learning model is needed to improve this skill. .The Pair Check learning model is a form of collaborative learning done in pairs, aiming to deepen or practice the learned material. Several studies show that the use of reading boards and letter cards can help improve students' reading skills, especially at the early stages in lower grades.